Bioactive Potential of Moroccan Ruta chalepensis: Polyphenol-Rich Extracts with Antioxidant and Anti-Staphylococcus aureus Activities - Hajar Sadrati; Bouchra Ezahidi; Abdelhakim Taha; Tarik Ainane; Ayoub Ainane; Younes Abbas; Sanaa Sabour Alaoui (Pandawa Institute, 2026)
The accelerating global crisis of antimicrobial resistance and oxidative stress-related diseases has intensified the search for novel therapeutic agents derived from natural sources. Polyphenolic compounds, abundant in many medicinal plants, have emerged as key candidates due to their potent antioxidant and antimicrobial properties. Ruta chalepensis L., a perennial species belonging to the Rutaceae family, is traditionally used in Mediterranean ethnomedicine for its antiseptic, anti-inflammatory, and digestive properties. In Morocco, where phytotherapy forms a cornerstone of rural healthcare practices, this species remains underexplored despite its wide distribution across the Middle Atlas and Rif regions. The present study aims to determine the phytochemical profile and its biological activity of Moroccan R. chalepensis by conducting a comprehensive organ-specific analysis. Methanolic extracts from the plant’s flowers, leaves, and stems were evaluated for their total phenolic content (TPC) and total flavonoid content (TFC) using the Folin-Ciocalteu and aluminum chloride colorimetric methods. Antioxidant potential was assessed through DPPH radical scavenging and ferric reducing antioxidant power (FRAP) assays, while antibacterial activity was tested against Staphylococcus aureus ATCC 29213, Pseudomonas aeruginosa ATCC 9721, and Streptococcus sp. CCMM/B24 using disc diffusion and minimum inhibitory concentration (MIC) protocols. Among all plant parts, floral extracts exhibited the highest TPC (160 ± 2.38 mg GAE/g DW) and TFC (30.1 ± 1.32 mg QE/g DW), alongside superior antioxidant activity (DPPH IC₅₀ = 23.1 ± 1.15 μg/mL). Notably, Gram-positive strains showed greater susceptibility to the extracts, with S. aureus being the most affected. These results underscore the therapeutic potential of Ruta chalepensis, particularly from Moroccan chemotypes, as a valuable source of natural antioxidants and antimicrobial agents. They also reinforce the importance of valorizing Morocco’s endemic medicinal flora in addressing contemporary biomedical challenges.